Implementing MRCRLB technique on modulation schemes in wireless rechargeable sensor networks - Mohit Angurala; Manju Bala; Sukhvinder Singh Bamber (Egyptian Informatics Journal, 2021)
As battery technology has not advanced as quickly as other technologies like semiconductor technology, energy efficiency is still one of the primary concerns in Wireless Sensor Networks (WSNs). One of the finest Wireless Energy Transfer (WET) technique is Magnetic Resonant Coupling (MRC) used to re-energize the nodes in WSNs. Recent advancements in MRC show that more than one node can be re-charged at the same time. This paper aims to exploit multiple nodes WET to overcome the issues pertaining to energy in Wireless Sensor Network (WSN). For transferring energy to various static sensor nodes deployed in a network, Unmanned Aerial Vehicle (UAV) is considered which travels inside a network and performs a process of re-charging. Further, WSNs being most acceptable face issues like: battery constraint, and congestion. Therefore, in order to address such issues, we have proposed MRCRLB (Magnetic Resonant Coupling Based Recharging and Load Balancing) scheme. Then, finally the proposed model is tested on various modulation schemes at the physical layer of WSNs to find out most appropriate modulation scheme type for lifetime extension model (MRCRLB).